Occlusion of a long-term transpleural biliary drainage tract using a gelatin pledget (Hep-Plug) - Kortes, Nikolas; Gnutzmann, Daniel; Konietzke, Philip; Mayer, Philipp; Sumkauskaite, Migle; Kauczor, Hans-Ulrich; Radeleff, Boris (CardioVascular and interventional radiology, 2017)
This case describes a technique used to close a long-term 14F transpleural biliary drainage catheter tract to prevent biliopleural fistula and further complications. We deployed a compressed gelatin foam pledget provided in a pre-loaded delivery device (Hep-Plug) along the intrahepatic tissue tract for sealing it against the pleural cavity. The device used is easy to handle and gives the Interventional Radiologist the possibility to safely manage and prevent complications after percutaneous transhepatic interventions.
Published 15 May 2017
Gesehen am 25.10.2018